The Discussions of Islamic and Conventional Tax Incentive Towards The Corporate Tax Planning Level In Malaysia - Nik Mohd Norfadzilah, Nik Mohd Rashid; Siti Nasuha, Muhmad; Mohd Hassan, CheHaat; Nadiah, Abd Hamid; Zarinah, Abdul Rasit (2017)
In Malaysia, there is lacking of Islamic tax incentive towards Islamic financial products in order to promote tax compliance among of corporate tax payers. Thus, this study is to investigate the selected Islamic financial products in order to estimate the most relevant influence towards the changes of corporate tax planning level. This is to increase the compliance level because when the corporate tax payer does not fully utilise the tax incentive given, they will involve in the tax fraud which is not illegal. The selected Islamic financial products are Bai BithamanAjil, Ijarah, Mudharabah and Al-Qardhul Hasan. This study also compared with the tax incentives given to the conventional financial products which are housing loan, leasing agreement, short term loan and conventional loan. In this study, the secondary of data is use and the sample of this study consist of Islamic and conventional financial institution listed on Bursa Malaysia from the year 2006 to 2016. This study will employ the following methods: 1) Pooled Ordinary Least Square method (Pooled OLS); 2) fixed effect method; and 3) random effect method. The findings of this study contribute to the literature on the Islamic tax incentives that could influence the corporate tax burden. Besides that, this study also contributes to the broad literature on the differences between Islamic tax incentives and conventional tax incentives towards corporate tax burden.